Моделювання процесу заморожування гарбузових овочів - Ялпачик, В. Ф.; Кюрчев, С. В.; Тарасенко, В. Г.; Yalpachik, Vladimir; Kyurchev, Sergey; Tarasenko, Vera (КНТУ, 2013)
Робота присвячена розробці математичної моделі процесу заморожування гарбузових овочів та її апробації по змінних в часі температурних полів, тривалості процесу і тепловим потокам шляхом порівняння розрахункових та експериментальних даних з метою контролю процесів в промислових умовах і подальшого вирішення задач енерго- та ресурсозбереження на агропромислових підприємствах.The work is devoted to developing a mathematical model of the process of freezing pumpkin vegetables and its approval by variable temperature fields over time, and duration of the heat flux by comparing the calculated and experimental data for process control in an industrial environment and further solve the problems of energy efficiency in the agro-industrial enterprises. Nonlinear interpolation formulated a mathematical model for the process of cooling and freezing pumpkin vegetables can expect changes in temperature fields and heat fluxes from the surface facilities refrigeration processing time. On the basis of testing of the formulated mathematical model obtained satisfactory results of testing.
Modeling of frozen pumpkin vegetables
Keywords: моделювання; заморожування; кабачок; гарбуз; фазове перетворення; теплообмін; modeling; freezing; squash; pumpkin; phase transformation; heat transfer